Design, Development, and Flight Test of a Small-Scale Cyclogyro UAV Utilizing a Novel Cam-Based Passive Blade Pitching Mechanism. Issue 2 (June 2013) - Adams, Zachary; Benedict, Moble; Hrishikeshavan, Vikram; Chopra, Inderjit
A cycloidal rotor is an innovative horizontal axis propulsion system, which is utilized in the present study to develop a fully-controllable flying aircraft (known as "Cyclogyro"). The present 535 gram cyclogyro uses a hybrid configuration with two cyclorotors and a horizontal tail rotor. Since a cycloidal rotor relies on cyclic blade pitching for producing thrust and also for control, designing a reliable pitch mechanism that can provide the required blade pitching kinematics (depending on the advance ratio) is extremely important. A novel blade pitch mechanism has been developed, which is passively driven by centrifugal force, and could potentially be adapted to generate the required pitching schedules for efficient operation over a range of advance ratios. A simplified flightworthy version of this mechanism was implemented in the present cyclogyro. The mechanism was able to generate the appropriate blade kinematics and the thrust required for the vehicle to hover. Also, the present mechanism is designed such that it is possible to vary both amplitude and phasing of the cyclic blade pitching. A novel control strategy was developed using blade pitch amplitude (thrust magnitude) control for roll, phasing (thrust direction) for yaw and tail rotor for pitch control. The control strategy was implemented using a three gram onboard processor, which was used to stabilize the vehicle without a pilot, through a closed-loop feedback control system. This is the first flight-capable cyclogyro reported in the literature to utilize cycloidal rotors having both pitch amplitude and phase control. The successful flight for the present vehicle also validates the flightworthiness of this completely passive pitch mechanism design, which has great potential for efficient forward flight.